Artificial Reefs in the Northern Gulf of Mexico: Community Ecology Amid the “Ocean Sprawl” - Schulze, Anja; Erdner, Deana L.; Grimes, Candace J.; Holstein, Daniel M.; Miglietta, Maria Pia (Frontiers in Marine Science, 2020)
The northern Gulf of Mexico has been an important source for crude oil and natural gas extraction since the 1930s. Thousands of fixed platforms and associated equipment have been installed on the Gulf of Mexico continental shelf, leading to a pervasive ‘ocean sprawl’. After decommissioning, hundreds of these structures have been converted to artificial reefs under the federal ‘Rigs-to-Reefs’ program, in addition to artificial reefs specifically designed to enhance fisheries and/or benefit the recreational diving industry. Apart from a few natural banks, which reach to approximately 55 ft below the surface, artificial reefs provide the only shallow-water hard substrate for benthic organisms in the deeper waters of the northern Gulf of Mexico. This vast expansion in available habitat has almost exclusively occurred over a relatively short span of time (~ 50 years). The ecological interactions of artificial and natural reefs in the northern Gulf of Mexico are complex. Artificial reefs in general, and oil and gas structures in particular, have often been invoked as stepping stones for non-native and invasive species (e.g. Tubastrea cup corals, lionfish). The pilings are covered with fouling communities which remain largely unstudied. While the risks of these fouling organisms for invading natural reefs are being broadly discussed, other impacts on the ecological and economic health of the Gulf of Mexico, such as the potential to facilitate jellyfish blooms or increase the incidence of ciguatera fish poisoning, have received less attention. Artificial reefs also provide ecosystem services, particularly as habitat for economically important fish species like red snapper. Here we revisit the potential role of artificial reefs as ‘stepping stones’ for species invasions and for fisheries enhancement. Beyond concerns about ecological effects, some of these topics also raise public health concerns. We point out gaps in current knowledge and propose future research directions.